2022
DOI: 10.1002/ncp.10845
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the impact of a carbohydrate loading drink on postprandial glycemic responses and gastric emptying in adults with prediabetes and type 2 diabetes mellitus

Abstract: Background: Preoperative carbohydrate (CHO) loading improves patient outcomes but is not extensively studied in individuals with diabetes mellitus (DM), resulting in limited professional recommendations. This study examined postprandial glycemic responses and gastric emptying rates following consumption of a CHO drink in adults with and without DM.Methods: A single-arm, nonrandomized pilot trial was conducted in adults without DM (non-DM) (47.5 ± 2.5 years), with pre-DM (55.8 ± 3.0 years), and with type 2 DM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In recent years, researchers began to pay attention to the risk of reflux aspiration after oral carbohydrate intake in diabetic patients. In several current research results, Cassady [13] et al assessed the gastric emptying rate by detecting the blood paracetamol content after drinking liquid mixed with carbohydrates and paracetamol before operation, and concluded that there was no significant difference in the gastric emptying rate between the diabetic group and the non-diabetic group. In the study of Lin Xinqiang et al [14] , after taking different amounts of carbohydrates orally before surgery, the gastric volume obtained from the gastric antrum area was measured by ultrasound to assess the risk of reflux aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers began to pay attention to the risk of reflux aspiration after oral carbohydrate intake in diabetic patients. In several current research results, Cassady [13] et al assessed the gastric emptying rate by detecting the blood paracetamol content after drinking liquid mixed with carbohydrates and paracetamol before operation, and concluded that there was no significant difference in the gastric emptying rate between the diabetic group and the non-diabetic group. In the study of Lin Xinqiang et al [14] , after taking different amounts of carbohydrates orally before surgery, the gastric volume obtained from the gastric antrum area was measured by ultrasound to assess the risk of reflux aspiration.…”
Section: Discussionmentioning
confidence: 99%